Revitalization of Pancasila Ideological Values Among the Young Generation As an Effort To Strengthen National Resilience - Aji, Muhammad Sajidin; Farhanuddin; Inggar Saputra (Universitas Negeri Semarang, 2025)
Pancasila as the basis of the Indonesian state contains values in every point that must be used as a guideline for the life of the Indonesian nation without exception the youth as the next generation of the nation who have the potential to realize national ideals. Youth are agents of change in Indonesia's development in the future, This is so that later Indonesian youth can compete with youth in other countries and can be strong and resilient in facing all national problems that are threats, obstacles, challenges and disturbances both from within and outside the country. Youth is an important key that plays an active role in strengthening national resilience. The focus of this study is the revitalization of Pancasila ideological values among the younger generation as an effort to strengthen national resilience. The research method used is literature study, which is a series of activities to search, read, record, review reports, and library materials that contain theories relevant to problems in revealing past events. The results of the study show that Indonesia's national resilience will be strong if elements of the nation can face all forms of threats, obstacles, challenges and disturbances that come from within and outside the country. One of the elements of the nation is the youth who become the next generation of the Indonesian nation in the future. So it is important to instill revitalization of the values of Pancasila ideology among Indonesian youth as a provision in facing competition amid the current of globalization.